Ocena rabe alkohola pri študentih zdravstvene nege s pomočjo vprašalnika AUDIT - Bogataj, Urška (Obzornik zdravstvene nege, 2013)
Introduction: Alcohol consumption among young people in Slovenia is becoming alarge-scale social and health problem. The purpose of this study was to determine the type of drinking behaviour and the degree of risk drinking among nursing students and to identify possible correlations and differences between the alcohol risk drinking level, gender, the form of study and age. Methods: The survey was conducted in the year 2012. AUDIT questionnaire was distributed to the first-year nursing students. The sample consisted of 182 completed questionnaires and was collected by non-random convenience sampling method. Along with the basic descriptive statistics, Student's t-test for independent samples, Chi-square test and Spearman's rank correlation coefficient were employed in the collection and analysis of data. Results: Results of the study show that male respondents and the group of full-time students more likely indulge in high risk drinking. A statistically significant difference was established between the average AUDIT points regarding gender (t = 5.852, p < 0.001) and the form of study (t = 3.024, p < 0.01). A moderate correlation was identified between the variable of age of participants and the total sum of points (r = -0.348, p < 0.001), where younger respondents reached higher points in total score. Discussion and conclusion: Survey results indicate different levels of risk drinking in a certain segment of full-time students, average age of 20 years. The male respondents and full- time students are more risky drinkers. The research findings indicate the need for open and comprehensive analysis of drinking patterns among students and the factors affecting their drinking behaviour. It is time to outline strategies to reduce college binge drinking and alcohol-related harm by coordinated effort and action.
Keywords: alcohol abuse; nursing care; risk level; stopnja tveganja; students; študentje; zdravstvena nega; zloraba alkohola